The Influence of Employee Retention and Organizational Commitment on Employee Turnover Intention at at PT. Indonesia Fastfood Tbk. at the KFC Ratulangi Makassar outlet - Dawenan, Leonard; Tangkeallo, Dian Intan; Pongtuluran, Althon K. (PINISI Discretion Review, 2024)
This study analyzes the influence of employee retention and organizational commitment on turnover intention at PT. Fastfood Indonesia Tbk. at the KFC Ratulangi Makassar outlet. Using a quantitative survey method with 33 respondents, the data were analyzed through multiple linear regression. The results show that employee retention (B = 0.314, p < 0.05) and organizational commitment (B = 1.159, p < 0.001) significantly influence the reduction of turnover intention. The constant value of -12.106 indicates that when employee retention and organizational commitment are both zero, turnover intention is predicted to be very low. Adjusted R2 of 0.874 indicates that 87.4% of the variability in turnover intention can be explained by employee retention and organizational commitment. The company is advised to enhance retention strategies and organizational commitment to maintain workforce stability and increase productivity.